Rasa percaya pada pasutri perkawinan jarak jauh - Naibaho, Saira Lastiar; Virlia, Stefani (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Couples have the responsibility in domestic life, communicating with each other, and accept any changes that occur in marital life. Physical separation between couples is severe, where the fulfillment of the task of marriage becomes ineffectivebecause couples can’t be met at all times. Trust becomes an important issue for coupleswith a distance apart, which can help couples maintain a household. This research is a phenomenological study, using interview techniques at the three couples aged 18-40 years who underwent commuter marriage since the beginning of the marriage with a maximum of 18 years of marriage. The results showed that trust in a commuter marriage can be seen from five aspects, such as openness, sharing, acceptance, support, and cooperate. There are two main factors that affect the subject remained with the conditions, commuter marriage is the economic factor and cultural factors that require women to take care her parents. In addition, there are other factors, such as the communication factor, the gratification of sexual needs, and marriage age.